The Human Person in the Anthropological Vision of Karol Wojtyla - Boluarte Drago, Analyda (2018)
It is not an irrelevant fact to be in front of a poet and dramatist, a philosopher, theologian, priest and later Pontiff, for the wealth of his intellectual production, bequeathed to the contemporary world, is avant-garde and fully relevant today. As a guiding principle, two texts by the author are considered: Love and Responsibility (1960) and Person and Action (1969). Also, as a reference, it will be taken into account the work of Dr. Juan Manuel Burgos Velasco, founder and president of the Spanish Association of Personalism and the Ibero-American Association of Personalism.